2017
DOI: 10.14569/ijacsa.2017.080252
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Evaluation of Social and Traditional Search Tools for Adhoc Information Retrieval

Abstract: Abstract-The nature of World Wide Web (www) has evolved over the passage of time. Easier and faster availability of Internet has given rise to huge volumes of data available online. Another cause of huge volumes of data is the emergence of online social networks (like Facebook, Twitter, etc.) which has actually changed the role of data consumers to data generators. Increasing popularity of these online social networks has also changed the way different web services used to be used. For example, Facebook messag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Moreover, it may take advantage of online presence society in order to identify specified field experts who may be help and response to people inquires. Hussain et al, (2017) argued that present-day net search engines are not fit to discover related information obtainable on the social platforms. Accordingly, people may tend to use social platforms for obtain the information.…”
Section: Social Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it may take advantage of online presence society in order to identify specified field experts who may be help and response to people inquires. Hussain et al, (2017) argued that present-day net search engines are not fit to discover related information obtainable on the social platforms. Accordingly, people may tend to use social platforms for obtain the information.…”
Section: Social Searchmentioning
confidence: 99%
“…Bulencea and Egger (2014) argued that Facebook is commonly used by tourists as a search engine for getting more information related to tourist attractions. Hussain et al, (2017) conducted research to find out the extent of the commonality of Facebook and Twitter as search engines, that may overtake Google in the near future. Results indicated that Google still dominates in the field of search engines, followed by Facebook and Twitter.…”
Section: Introductionmentioning
confidence: 99%